2022
DOI: 10.3390/nu14102105
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Risk Assessment Scores Effectively Predict Mortality in Critically Ill Patients with Severe COVID-19

Abstract: Background: Malnutrition predicts a worse outcome for critically ill patients. However, quick, easy-to-use nutritional risk assessment tools have not been adequately validated. Aims and Methods: The study aimed to evaluate the role of four biological nutritional risk assessment instruments (the Prognostic Nutritional Index—PNI, the Controlling Nutritional Status Score—CONUT, the Nutrition Risk in Critically Ill—NUTRIC, and the modified NUTRIC—mNUTRIC), along with CT-derived fat tissue and muscle mass measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 43 publications
(55 reference statements)
3
18
0
Order By: Relevance
“…In regard to the predictive role of nutritional markers, in the meta-analysis published by Hung et al [ 52 ], in which 13 studies were included, and a total number of 4204 COVID-19 patients, it was demonstrated that PNI is a predictor of mortality. Moreover, research by Bodolea et al [ 53 ] resulted in PNI > 28.05 (HR:0.91; p = 0.01), and a CONUT Score > 7.5 (HR:1.15; p = 0.01) becoming associated with mortality, in the case of 90 COVID-19 patients with the severe form.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In regard to the predictive role of nutritional markers, in the meta-analysis published by Hung et al [ 52 ], in which 13 studies were included, and a total number of 4204 COVID-19 patients, it was demonstrated that PNI is a predictor of mortality. Moreover, research by Bodolea et al [ 53 ] resulted in PNI > 28.05 (HR:0.91; p = 0.01), and a CONUT Score > 7.5 (HR:1.15; p = 0.01) becoming associated with mortality, in the case of 90 COVID-19 patients with the severe form.…”
Section: Discussionmentioning
confidence: 98%
“…In terms of nutritional status, the prognostic nutritional index (PNI) and controlling nutritional status (CONUT) scores are associated with disease severity and have a predictive role in COVID-19 patient mortality [ 52 , 53 , 54 , 55 , 56 , 57 ]…”
Section: Introductionmentioning
confidence: 99%
“…Our study preliminarily illustrated the clinical guidance of the CONUT score as a reliable nutritional screening tool. Similarly, CONUT has been demonstrated to have good prognostic value in cancers and other infections [ 35 , 55 , 56 ]. Although the exact mechanism is uncertain, this association may be explained by the nutritional and immune-related parameters in CONUT [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…As of today, nutritional assessment can be achieved effectively with different measurable immunonutritional screening tools (INST), such as Controlling Nutritional Status (CONUT) [ 32 ], Nutritional Risk Index (NRI) [ 33 ], and Naples Prognostic Score (NPS) [ 34 ]. These tools have demonstrated promising potential in the nutritional and prognostic assessment of various diseases [ 35 , 36 , 37 ]. Another major advantage of them is the availability and feasibility of the included parameters in many hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…Survived patients had a lower score than deceased individuals. Previous studies have demonstrated that NUTRIC can be used as a predictor of malnutrition risk and mortality in critically ill COVID-19 patients and a higher NUTRIC score was associated with a higher mortality rate [ 52 55 ].…”
Section: Discussionmentioning
confidence: 99%